1970
DOI: 10.4314/gjpas.v21i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profile of the endocarp and exocarp of yellow monkey cola (Cola lepidota)

Abstract: The chemical profile of the Endocarp and Exocarp of yellow monkey cola (Cola lepidota) were investigated using chemical analysis. The results of proximate analysis showed that the endocarp has the following compositions: moisture (20.00+0.10%W/W), ash (4.00+0.11%DM), crude fibre (36.00+0.12%DM), crude fat (16.00+0.11%DM), crude protein (22.84+0.12%DM), available carbohydrate (21.16+0.12%DM) and the energy value (320.00+0.01kcal/100g) while the exocarp contained moisture (22.00+0.12%W/W), ash (8.00+0.11%DM), cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…[2] also indicated that calcium and magnesium were the most abundant minerals in the fruit pulp of both C. parchycarpa and C. lepidota. This result reported in this study was also corroborated by Osabor et al [8] who reported high amount of some essential minerals in the endocarp of C. lepidota.…”
Section: Mineral Composition Of Cola Lepidotasupporting
confidence: 92%
See 1 more Smart Citation
“…[2] also indicated that calcium and magnesium were the most abundant minerals in the fruit pulp of both C. parchycarpa and C. lepidota. This result reported in this study was also corroborated by Osabor et al [8] who reported high amount of some essential minerals in the endocarp of C. lepidota.…”
Section: Mineral Composition Of Cola Lepidotasupporting
confidence: 92%
“…In Nigeria, Monkey kola is mostly consumed fresh and like most fruits and vegetables, it has a very short life span probably due to its high moisture content Ene-Obong et al [2]. Cola lepidota is of great importance to the vulnerable groups, the fruit is a good source of protein, fat, carbohydrate and minerals [8] and constitutes one of the best tools for preventing diseases caused by lack or insufficient supply of vitamins in diet [9]. Nutritionally, the fruits are believed to contain beta carotene which acts as antioxidant [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the concentration of K and Ca in ginger are higher while in Roselle, the concentration of Ca, K and Mg are higher Fig ( 1). Mg, Cu, Se, Zn, Fe, Mn and Mo are important co-factors found in the structure of certain enzymes and are indispensable in numerous biochemical pathways (8).Mg is the most important metal that is required in the body, it is used to correct absorption of K and the efficient functioning of the enzyme (9). Ca, Mg and P are also essential for bone and teeth formation (10).…”
Section: Resultsmentioning
confidence: 99%
“…Cola rostrata was richer in magnesium, zinc and calcium contents compared to C. parchycarpa (Table 2). Osabor et al (2015) also reported that calcium was the most predominant element in the endocarp of Cola lepidota and that mineral elements are needed in the body for proper functioning. Calcium plays fundamental roles in most reactions involving phosphate transfer, believed to be essential in the structural suability of nucleic acid and intestinal absorption (Appel, 1999).…”
Section: Discussionmentioning
confidence: 96%